A COLORFUL DIET IS NEEDED TO ENHANCE ACADEMIC PERFORMANCE OF THE CHILDREN - Hussain, Munira M. (International Journal of Research -GRANTHAALAYAH, 2014)
Colors contain phytochemicals substances occur naturally only in plants and provide health benefits beyond those that essential nutrients provide. A nutritionally adequate diet is essential for optimal growth and development. Childhood and adolescence are periods of continuous growth and development. So, in this study Phytochemical intake of the school going children was computed by counting the number of serving of colourful fruits and vegetables in their diet per week and association of phytochemical intake status with academic performance was found out. Obtained results showed that the distribution of children among different categories of academic performance as per their phytochemical intake status was found significant. Children taking high phytochemical foods were found more in better academic performance category in comparison to children taking low phytochemical foods. Colourful phytonutrients have tremendous health benefits for the brain. Phytonutrients impart colour to fruits and vegetables and are the basis of the recommendation to "eat your colours. The current recommendation of 5-9 servings of fruits and vegetables is not being met with most children. So, taking colourful diet is important for over all wellbeing of the children.